Internalisasi Teori Baca Tulis Arab Melayu dalam Pembelajaran Siswa di Sekolah Dasar - Eka Trianingsih; Sri Mawaddah (Pustaka Digital Indonesia, 2025)
The urgency of this study is to analyze the internalization of reading and writing skills in the Jawi script (Arab-Malay script) within the learning process of elementary school students at SD Negeri 1 Banda Aceh. This research employs a descriptive qualitative approach using participatory observation, semi-structured interviews, and document analysis. The findings indicate that integrating the Arab-Malay script into culturally based learning significantly enhances students’ motivation and comprehension. Interactive learning methods, such as the use of digital applications and the Imla’ (dictation) technique, have proven effective in facilitating students’ gradual internalization of the script. Furthermore, the teacher’s role as a facilitator, along with a culturally responsive curriculum, greatly contributes to the success of the learning process. The study also highlights that combining the Jawi script with other subjects, such as the Indonesian Language and Islamic Religious Education, improves literacy skills while reinforcing students’ cultural and religious identities. However, several challenges remain, including limited instructional time and a lack of engaging learning media. These obstacles indicate the need for more innovative and integrated strategies to optimize the teaching of the Arab-Malay script in elementary education. The results of this study contribute to the development of culturally responsive education and the preservation of local linguistic heritage. Further research is recommended to explore the long-term impact of Jawi script learning on students’ academic achievement and cultural identity development.